Revitalization of The Sasak Local Wisdom Values for The Social Harmony in Berinding Central Lombok - Sakinaturrahmi, Yulia; Sudrajat, Sudrajat (el Harakah: Jurnal Budaya Islam, 2025)
Globalization has brought diverse cultures and values that have gradually eroded the local wisdom of the Sasak tribe. This decline—exacerbated by globalization, the COVID-19 pandemic, weak educational transmission, and cultural change—has prompted community leaders and government actors to intensify preservation efforts. Previous studies have largely examined Sasak local wisdom from anthropological or cultural perspectives, focusing on documentation or historical description. However, few have analyzed the concrete and collaborative strategies undertaken by multiple community stakeholders to sustain and revitalize these values amid modern globalization. This study fills that gap by investigating how village governments, religious leaders, traditional figures, and youth organizations collectively work to preserve and renew Sasak local wisdom as a living cultural system. Using a qualitative ethnographic approach, this research employs observation, interviews, and documentation as data collection methods. The findings reveal several strategic initiatives: (1) village heads organize cultural festivals, commemorate village anniversaries with local themes, restore historical sites, and collaborate on curriculum development; (2) religious leaders strengthen moral and spiritual awareness through weekly studies and Islamic holiday celebrations; (3) traditional leaders conduct training on sorong serah aji krame, traditional etiquette, and cultural identity; and (4) youth leaders establish the “Remaje Sasak” community as a hub for information exchange, learning, and the practice of local wisdom. These collective efforts provide a platform for the Sasak people—especially the younger generation—to preserve, internalize, and embody the values rooted in their cultural heritage. The study’s implications highlight that integrated collaboration among local stakeholders offers a replicable model for other communities seeking to protect and sustain their cultural identity amid the transformative pressures of globalization. Globalisasi telah membawa beragam budaya dan nilai-nilai baru yang secara perlahan mengikis kearifan lokal masyarakat Suku Sasak. Kemerosotan ini—yang diperparah oleh arus globalisasi, pandemi COVID-19, lemahnya transmisi pendidikan, dan perubahan budaya—telah mendorong para pemimpin masyarakat serta pemerintah desa untuk meningkatkan upaya pelestarian kearifan lokal. Penelitian sebelumnya umumnya mengkaji kearifan lokal Sasak dari perspektif antropologis atau kebudayaan dengan penekanan pada dokumentasi dan deskripsi historis. Namun, hanya sedikit yang menelaah strategi konkret dan kolaboratif yang dilakukan oleh berbagai pemangku kepentingan masyarakat dalam mempertahankan serta merevitalisasi nilai-nilai tersebut di tengah arus globalisasi modern. Penelitian ini mengisi kesenjangan tersebut dengan menganalisis bagaimana pemerintah desa, tokoh agama, tokoh adat, dan organisasi kepemudaan bekerja sama untuk melestarikan dan memperbarui kearifan lokal Sasak sebagai sistem budaya yang hidup. Penelitian ini menggunakan pendekatan kualitatif dengan metode etnografi serta teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan beberapa inisiatif strategis, yaitu: (1) kepala desa menyelenggarakan festival budaya, memperingati hari jadi desa dengan tema kearifan lokal, memulihkan situs bersejarah, dan bekerja sama dalam pengembangan kurikulum; (2) tokoh agama memperkuat kesadaran moral dan spiritual melalui pengajian rutin dan perayaan hari besar Islam; (3) tokoh adat memberikan pelatihan tentang sorong serah aji krame, etika tradisional, dan identitas budaya; serta (4) tokoh pemuda membentuk komunitas “Remaje Sasak” sebagai pusat informasi, pembelajaran, dan praktik kearifan lokal. Upaya kolektif ini menjadi wadah bagi masyarakat Sasak—khususnya generasi muda—untuk melestarikan, menginternalisasi, dan mengamalkan nilai-nilai luhur yang tertanam dalam warisan budaya mereka. Implikasi penelitian ini menegaskan bahwa kolaborasi terpadu antar pemangku kepentingan lokal dapat menjadi model bagi komunitas lain dalam menjaga dan memperkuat identitas budaya di tengah tekanan globalisasi.